Manajemen Program Gizi Analisis Situasi Gizi dan Penentuan Prioritas Masalah Gizi di Kecamatan Meureubo - Dina Mariatun; Rahmatul Sariyanti; Erika Wisanda; Dina Pratiwi; Chika Amelya Rossa; Silvia Agusdiana; Hamliatus Sakinah HSB; Ranita Suri Dewi (Indo Publishing, 2026)
Chronic Energy Deficiency (CED) among pregnant women remains an important nutritional problem because it increases the risk of pregnancy complications, low birth weight infants, prematurity, and stunting. This study aimed to analyze the situation of CED among pregnant women in Meureubo District, West Aceh Regency. A descriptive study with a cross-sectional approach was conducted using secondary data obtained from e-PPGBM reports, the West Aceh Health Profile, and health center records. The analysis focused on describing the prevalence of CED and its contributing factors. The results showed that the prevalence of CED among pregnant women in Meureubo District reached 57.4%, which was higher than the provincial and national averages. Contributing factors included household economic conditions, low nutrition knowledge, food taboos during pregnancy, and limited access to nutritious foods. Therefore, interventions such as nutrition education, supplementary feeding programs, regular nutritional monitoring, and multisectoral support are needed to reduce the prevalence of CED. In conclusion, CED among pregnant women is a priority nutritional problem requiring sustainable interventions in Meureubo District.